GIS/GPS solutions as efficient tools for sustainable management of vineyards in Kosovo - Kuka, Ymer; Ameti, Perparim; Bandrova, Temenoujka (Geodesy and Cartography, 2019)
The main objective of this paper is to analyze and develop a GIS system that includes all necessary information obtained by using GPS and mobile GIS techniques as well. Since several techniques for information management exist, the aim is how to integrate them for a sustainable management of vineyards areas in Kosovo. It has been designed a system, which is able to produce maps, make various analyses based on the requests of the specific users and offers trend orientation for decision making. The JAVA programming language has been used. This provides the most possible flexibility in the data flow and data management. The structure of the data base is proposed to be designed in that way that the textual and geometric data have been processed in a unique data base in PostGIS PostgreSQL technology.Web GIS technology presented in this paper, shows an advantage comparing to the desktop based technology since it enables an access in real time. Foremost, the application offers an access depending on the roles and privileges for different users. Development of a WEB application for viticulture management will improve the efficiency and decision making process as well.Results show numerous capabilities of GIS methodologies to manage the agricultural crops, in this particular case, the vineyards. Further, the results provide insight into information management in a single system and serve as a basis for similar researches in other areas of agriculture in the future.